Essentials of psychiatric mental health nursing : a communication approach to evidence-based care - Varcarolis, Elizabeth M.; Halter, Margaret J. [ (Margaret Jordan)] (Saunders/Elsevier, 2009)
Offers an approach to psychiatric mental health that provides you with a way to understand the subject of psychiatric nursing. This title includes two themes of psychiatric mental health nursing: the 'How' of Communication and the 'Why' of Evidence. It also includes explanations of the research that applies to psychiatric nursing issues